How does the smartphone usage of college students affect academic performance?. (19th September 2018) - Han, Sunyoung; Yi, Yong Jeong
Abstract: The present study aims to investigate the effects of smartphone use by college students on their perceived academic performance. Using five hypotheses derived from the literature related to smartphone use, the initial model was set up for path analysis to reveal the relationships among variables regarding college students' smartphone use in the academic setting. Moreover, multiple group analyses were additionally conducted to verify whether students exhibited different relationships in the hypothesized model depending on their majors. The results from path analyses showed that all path coefficients were positive and statistically significant, which indicated that all five hypothesized paths were supported. Above all, the results from multiple group analysis showed that one path (from Behavioural Intention to Use Smartphone to Academic Performance ) differed significantly across groups. The findings from the current study provide educational policymakers and educators with information on how smartphone utilization in learning activities influences students' academic performance. Lay Description: What is already known about this topic: Smartphones foster interaction with people and multitasking. College students use smartphones as learning aids in e‐learning and web‐based learning. College students have high smartphone self‐efficacy. Smartphones have both positive and negative effects on academic performance. What this paper adds: College students' interaction competency influences behavioural intention for using smartphones for academic activities. College students' smartphone self‐efficacy has positive impacts on their behavioural intention for using smartphones for academic purposes. College students' behavioural intention to use smartphones positively influences perceived academic performances. Students' behavioural intention to use smartphones presents distinct impacts on academic performances depending on their major fields: natural science and humanities. Implications for practice and/or policy: Educational policymakers and educators may benefit information on how smartphone utilization in learning activities influences students' academic performances. The instrument developed in the present study could be used for future studies on smartphone use and students' psychological factors such as self‐efficacy and behavioural intention to use smartphones.